2002
DOI: 10.1074/jbc.m209876200
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Regulation of Tenascin-R Glycosylation in the Cerebellum

Abstract: The cellular adhesion molecule tenascin-R is a multifunctional extracellular matrix component expressed exclusively in the central nervous system. The expression of tenascin-R by oligodendrocytes and small interneurons in the hippocampus and cerebellum is highly regulated during development of these regions. This complex glycoprotein displays both adhesive and antiadhesive properties that contribute to the formation and maintenance of synapses. We have determined that tenascin-R associated with Purkinje cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…Furthermore, GalNAc-4-sulfotransferase and protein-specific ␤1,4GalNAc-transferase activities are also expressed in the brain (27), and Cys-Fc reactive material is particularly prominent in the cerebellum and hippocampus (15,16). We recently reported that the extracellular matrix protein tenascin-R is modified with terminal GalNAc-4-SO 4 and can be bound to immobilized Cys-Fc (15).…”
Section: Sorla/lr11 Produced In Kidney and Brain Is Bound By Immobilizedmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, GalNAc-4-sulfotransferase and protein-specific ␤1,4GalNAc-transferase activities are also expressed in the brain (27), and Cys-Fc reactive material is particularly prominent in the cerebellum and hippocampus (15,16). We recently reported that the extracellular matrix protein tenascin-R is modified with terminal GalNAc-4-SO 4 and can be bound to immobilized Cys-Fc (15).…”
Section: Sorla/lr11 Produced In Kidney and Brain Is Bound By Immobilizedmentioning
confidence: 99%
“…Because the Cys-rich domain of the Man/GalNAc-4-SO 4 receptor is highly specific for terminal sulfated sugars such as ␤1,4-linked GalNAc-4-SO 4 (25,28,29), we utilized a chimeric protein consisting of the Cys-rich domain and the Fc domain of human IgG, Cys-Fc, to immunostain tissue sections for the presence of glycoproteins bearing terminal ␤1,4-linked GalNAc-4-SO 4 (15,25). Cells comprising collecting ducts in the medulla and papilla of the mouse kidney are intensely stained (Fig.…”
Section: Cys-fc Reactive Materials Is Located In the Medulla And Papilmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of glycoproteins synthesized in other tissues that are also selectively modified with terminal GalNAc-4-SO 4 , for example, the LDL-receptor homolog SorLA/LR11 expressed in the kidney and the brain (48) and tenascin-R expressed in the brain (49). It is possible that additional differences between WT and GalNAc-4-ST1 -/-mice will be identified upon further examination; however, none of the other glycoproteins identified thus far as bearing structures terminating with SO 4 -4-GalNAcβ1,4GlcNAc would be expected to have an impact on steroid hormone production or reproduction.…”
Section: Figure 10mentioning
confidence: 99%
“…However, another type of nonreducing terminal glycan structure that is less well understood but now appears to also be expressed by many organisms, including mammals, is based on the LacdiNAc (LDN) sequence GalNAc␤1-4GlcNAc-R, which can also occur within 4-O-sulfated, ␣1,3-fucosylated, or ␣2,6-sialylated derivatives. LDN-type glycans play vital roles in regulating the circulatory half-life of pituitary glycoprotein hormones (1-3) and other glycoproteins (4,5), including tenascin-R produced by oligodendrocytes and small interneurons in the hippocampus and cerebellum (6). Other glycoproteins containing LDN-type glycans include human glycodelin, a human glycoprotein with potent immunosuppressive and contraceptive activities (7,8), and zona pellucida glycoproteins from murine eggs (9).…”
mentioning
confidence: 99%